Adjuvant chemotherapy of resistant high risk choriocarcinoma - Đuričić, Tamara; Mandić, Aljoša; Gutić, Bojana; Prvulović Bunović, Nataša; Stanulović, Nevena (Archive of Oncology, 2021)
SUMMARYChoriocarcinoma is a subtype of gestational trophoblastic disease. It is a very rare neoplasm, with incidence of about 1 case in 40.000 pregnancies. Gestational form of choriocarcinoma arises most commonly after abortion, while non-gestational form develops from pluripotent germ cells. Choricarcinoma is highly malignant and highly chemosensitive type of tumor.A 43-year-old patient diagnosed with extra uterine pregnancy in September 2017 was treated with Methotrexate with no response and had surgical removal of right Fallopian tube. Choriocarcinoma was diagnosed one and a half year after extra uterine pregnancy. Radiological imaging before treatment showed pulmonary and inguinal lymph node metastases and tumor invasion of the anterior uterine wall. Surgery was performed due to heavy bleeding and uterine wall invasion. As high risk patient she received chemotherapy. She was followed radiologically and her serum β-HCG was monitored. Refractivity to the chemotherapy protocol during treatment was observed. Therapy response was achieved after administration of EMA-EP protocol modification i.e. three consecutive negative follow-up values of β-HCG were obtained and radiological findings were disease free. One month after treatment patient had no signs of disease and β-HCG level was normal.
Keywords: gestational trophoblastic disease; chemotherapy; choriocarcinoma